A new species of the genus Guillarmodia (Mollusca: Gastropoda: Pulmonata: Spiraxidae) from northeastern Mexico - Correa-Sandoval, Alfonso; Barrientos-Lozano, Ludivina; Strenth, Ned E. (Instituto de Ecología, A.C., 2018)
A new land snail, Guillarmodia (Guillarmodia) marcelae n. sp., Correa-Sandoval, Barrientos-Lozano & Strenth is described from the mountains of Sierra Los Soldados state of Tamaulipas in northeastern Mexico. This new species differs from other regional species of Guillarmodia by its smaller size and distinctive subsutural striations. Habitat information of the species and geographic distribution of related taxa are provided.